EFEKTIVITAS PELAKSANAAN PERATURAN MAHKAMAH AGUNG NOMOR 7 TAHUN 2022 DALAM PENYELESAIAN PERKARA PERCERAIAN DI PENGADILAN AGAMA KELAS 1A SEMARANG - Maulida Sasy Kirana; Efi Yulistyowati; Agus Saiful Abib (Fakultas Hukum, Universitas Semarang, 2025)
Supreme Court Regulation Number 7 of 2022 aims to realize the principle of fast, simple, and low-cost justice implementation. This article will discuss the effectiveness of the implementation of the Supreme Court Regulation in resolving divorce cases at the Class 1A Religious Court of Semarang, and the factors that influence the effectiveness of the implementation of the Supreme Court Regulation. This type of research is empirical juridical, with analytical descriptive research specifications. The sample is the implementation of Supreme Court Regulation Number 7 of 2022 in resolving divorce cases at the Class 1A Religious Court of Semarang in 2023-2024. The data used are primary data and secondary data, which are collected through interviews, literature studies, and documentation studies. The data is then analyzed qualitatively. The results of the study indicate that the Implementation of Supreme Court Regulation Number. 7 of 2022 in resolving divorce cases at the Class 1A Religious Court of Semarang is quite effective, but not yet optimal. The factors that influence the effectiveness of the implementation of the Supreme Court Regulation are: (1) Internal factors: the availability of adequate facilities and infrastructure to support the implementation of E-Court, but there are still shortcomings in socialization, there are no pamphlets, guidebooks, brochures, visual media, and trial applications that can be accessed to practice using E-Court, (2) External factors: many people do not yet understand the procedures and benefits of E-Court, not all advocates have been able to adapt to the E-Court system, internet network access is uneven in various regions, and the background of human resources is diverse. Abstrak Peraturan Mahkamah Agung Nomor 7 Tahun 2022 bertujuan untuk mewujudkan prinsip pelaksanaan peradilan yang cepat, sederhana, dan biaya ringan. Artikel ini akan membahas efektivitas pelaksanaan Peraturan Mahkamah Agung tersebut dalam menyelesaikan perkara perceraian di Pengadilan Agama Kelas 1A Semarang, dan faktor-faktor yang mempengaruhi efektivitas pelaksanaan Peraturan Mahkamah Agung tersebut. Jenis penelitian ini adalah yuridis empiris, dengan spesifikasi penelitian diskriptif analitis. Sampelnya adalah pelaksanaan Peraturan Mahkamah Agung Nomor 7 Tahun 2022 dalam penyelesaian perkara perceraian di Pengadilan Agama Kelas 1A Semarang tahun 2023-2024. Data yang dipakai adalah data primer dan data sekunder, yang diambil dengan cara wawancara, studi Pustaka, dan studi dokumentasi. Data tersebut kemudian dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa Pelaksanaan Peraturan Mahkamah Agung Nomor. 7 Tahun 2022 dalam menyelesaikan perkara perceraian di Pengadilan Agama Kelas 1A Semarang, cukup efektif, tetapi belum optimal. Faktor-faktor yang mempengaruhi efektivitas pelaksanaan Peraturan Mahkamah Agung tersebut adalah : (1) Faktor internal : tersedianya sarana dan prasarana yang memadai untuk mendukung penyelenggaraan E-Court, namun masih ada kekurangan dalam sosialisasi, tidak ada pamflet, buku panduan, brosur, media visual, dan aplikasi percobaan yang dapat diakses untuk berlatih menggunakan E-Court, (2) Faktor eksternal : banyak masyarakat yang belum memahami prosedur dan keuntungan E-Court, para advokat belum seluruhnya bisa beradaptasi dengan sistem E-Court, akses jaringan internet yang tidak merata di berbagai daerah, dan latar belakang SDM yang beragam.